2015
DOI: 10.1016/j.alcr.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Realization of fertility intentions by different time frames

Abstract: This paper focuses on the realization of positive fertility intentions with different time frames. The analyses are based on a unique combination of survey data and information from Norwegian administrative registers on childbearing in the years following the complete selected sample. Guided by the theoretical and empirical framework of the Theory of Planned Behavior (TPB), the results suggest that a fertility intention's time frame is relevant for childbearing behaviour, but the patterns are somewhat differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 26 publications
5
52
0
Order By: Relevance
“…Our findings showed that age was significantly and negatively associated with childbearing intention. This finding is consistent with existing evidence showing that age has an effect on childbearing [ 4 , 29 , 30 ]. For instance, a study by Kodzi et al showed that with each 1-year increase in age at the first childbearing, fertility dropped 3% in women [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings showed that age was significantly and negatively associated with childbearing intention. This finding is consistent with existing evidence showing that age has an effect on childbearing [ 4 , 29 , 30 ]. For instance, a study by Kodzi et al showed that with each 1-year increase in age at the first childbearing, fertility dropped 3% in women [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous researches on different populations [ 12 , 30 ], the results of our study indicated that more positive attitudes toward having a child were associated with more favorable intentions to have a child. Most of the literature on the TPB-based framework, emphasize the importance of attitude as a basic influential construct in the prediction of behavior [ 7 , 8 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other findings of the present study demonstrated that attitude and subjective norms also predict the intention of childbearing among women, which is consistent with the results of similar studies [7]. In fact, if a woman has a positive attitude toward childbearing and the important people in her life encourage her in this regard, it can significantly contribute to the woman’s childbearing intention [15]. In some countries, religious beliefs regarding childbearing increase the intention to have children [16].…”
Section: Discussionsupporting
confidence: 92%
“…For most Chinese families, childbearing is one of the most important functions of marriage and family. Considering the existing research, whether there is the influence of disease or not, people's fertility intention is strongly related to age, and questionnaire is mainly designed to understand the fertility intention of ADPKD patients and the cognition of PGT technology, so the control study with healthy people was not included in the study design [27,28]. This study showed that only 45.0% (117/260) of ADPKD patients at reproductive age had fertility intentions.…”
Section: Fertility Willingnessmentioning
confidence: 99%